2004
DOI: 10.1002/jbm.a.30098
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic interactions as a predictor for osteoblast attachment to biomaterials

Abstract: The present study utilizes zeta (zeta)-potential analysis as an indicator of bonding of osteoblasts and whole bone to various biomaterials. Common metal alloys (316L stainless steel, CoCrMo, and Ti6Al4V) and bioceramics (hydroxyapatite and beta-tricalcium phosphate) used in orthopedic applications were suspended in particulate form in physiologic saline, both as-received and supplemented with bovine serum albumin (BSA). Metal alloys were also treated with NaOH washing to study the effect of such a surface trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…If that were true, the process would be diffusion-or surface-reaction-controlled and consequently highly dependent on temperature and pH, which has indeed been experimentally confirmed. It was also shown that washing the precipitate at the stage where it is still amorphous increases the final Ca/P ratio because of removing the acidic layers of H x PO xÀ3 4 ions surrounding the growing particles (as already mentioned, it appears that H x PO xÀ3 4 ions are more effectively absorbed onto HAP particles than Ca 2þ , and can be therefore used for manipulating their f-potential 202,203 and thus controlling the efficiency of adsorption of biomolecules and cells thereto 204 ), thereby validating the effect of exchange of ions between the solution and the precipitate on the final identity of the latter.…”
Section: Mechanism Of Formation Of Hap By Precipitationmentioning
confidence: 87%
“…If that were true, the process would be diffusion-or surface-reaction-controlled and consequently highly dependent on temperature and pH, which has indeed been experimentally confirmed. It was also shown that washing the precipitate at the stage where it is still amorphous increases the final Ca/P ratio because of removing the acidic layers of H x PO xÀ3 4 ions surrounding the growing particles (as already mentioned, it appears that H x PO xÀ3 4 ions are more effectively absorbed onto HAP particles than Ca 2þ , and can be therefore used for manipulating their f-potential 202,203 and thus controlling the efficiency of adsorption of biomolecules and cells thereto 204 ), thereby validating the effect of exchange of ions between the solution and the precipitate on the final identity of the latter.…”
Section: Mechanism Of Formation Of Hap By Precipitationmentioning
confidence: 87%
“…The larger adhesion forces observed for SiHA could be due to its larger Hamaker constant versus HA and could play a role in the bone-biomaterial bonding. The greater attractive van der Waals force for SiHA could help overcome the electrostatic double-layer repulsion of osteoblasts with negatively charged cell membrane surfaces (e.g., surface potentials of MC3T3-E1 mouse osteoblasts suspended in physiological saline were measured through ultrasonic attenuation spectroscopy to vary from Ϫ29.4 to Ϫ52.4 mV at pH 7.3-7.5) 47 and the net negative charge of most serum proteins. 48 In general, adhesion interactions have contributions from surface forces such as van der Waals, surface charge, and hydrophobicity as well as surface topology, which can be difficult to deconvolute.…”
Section: Discussionmentioning
confidence: 99%
“…16,23,24 Since osteoblasts are negatively charged, 25 they are electrostatically repelled by the negatively charged titanium surface as long as some other attractive forces are not present in the system. Recently, a possible mechanism of osteoblast adhesion to the implant surface was proposed on the assumption that positively charged proteins 25,26 or proteins with positively charged tips, ie, a quadrupolar internal charge distribution 15 attached to the negatively charged implant surface, serve as a substrate for the subsequent attachment of negatively charged osteoblasts. In order to predict the orientation of proteins with positively charged tips near a charged implant surface, Monte Carlo simulations of the distribution and the orientation of charged spheroidal proteins in the vicinity of a charged titanium surface were performed.…”
Section: Adhesion Of Proteins To a Titanium Surfacementioning
confidence: 99%